Polyphenols and theobromine in cacao (Theobroma cacao): Compositional changes across variety, growing region, fermentation, drying and roasting (Scientia Agropecuaria, 2025)
In recent years, cacao and its derivatives have gained significant attention due to their potential health benefits. The primary bioactive compounds in cacao are polyphenols and methylxanthines, predominantly represented by theobromine. Their concentrations vary widely, influenced by cacao variety, growth region, and postharvest processing. Fermentation typically leads to a marked decrease in polyphenols and theobromine, with further reductions during drying and roasting. This review aims to consolidate current knowledge on how these factors affect compound levels, providing insights crucial for optimizing practices to enhance the health benefits and quality of cacao products. Literature consistently shows that cacao properties are shaped by genetics, environmental conditions, and processing stages. Moreover, the unique polyphenol and theobromine profiles can serve as distinctive fingerprints to differentiate cacao origins. Understanding these dynamics is essential for improving both nutritional value and industrial applications.
Keywords: cacao chemical composition; polyphenolic compounds; cacao varieties; cacao methylxanthines; postharvest operations; phenolic content; microbial fermentation